The Effect of Illustrated Glossaries of Plant Life Material on Students’ Learning Motivation - Purnama, Egi; Rumalolas, Nuryanti; Nebore, Idola; Erari, Semuel (Program Studi Pendidikan Biologi FKIP Universitas Pakuan, 2025)
The National Education Goals play an important role in realizing the nation’s ideals through various learning resources and media accessible to students in schools. Strong learning motivation serves as a fundamental basis for developing students’ potential to become faithful, morally upright, and responsible individuals. One way to enhance learning motivation is by providing engaging learning media, such as glossaries that help students better understand scientific terms. This study aims to examine the effect of illustrated glossaries on students’ learning motivation in the topic of the plant world. A quasi experimental method with a pretest-posttest control group design was employed. Two classes participated in the study: an experimental group that used illustrated glossaries to assist in understanding scientific terms and a control group that did not use any glossary, both using the same biology textbook. Data were collected using a learning motivation questionnaire measuring eight indicators, including perseverance, persistence, interest, independent work, boredom with routine tasks, maintaining opinions, determination, and problem solving enthusiasm. The results indicate that the use of illustrated glossaries significantly increased students’ learning motivation compared to those who did not use them. Motivation indicators in the experimental group ranged from high to very high categories. In conclusion, illustrated glossaries effectively enhance students’ learning motivation in plant world material. It is recommended that illustrated glossaries be implemented across various educational levels and fields to support accurate and consistent scientific terminology, helping students keep pace with scientific advancements.